The Role of Intellectual Capital in Sustainable Performance: Evidence from Iraq - Al-Gburi Hayder Jameel Ahmed,; Mohsin Sara AbdulalKareem, (Technium Social Sciences Journal, 2025)
This study aims to explain the impact of intellectual capital in sustainable performance for a sample of telecommunication corporations listed on the Iraqi Stock Exchange. Our research sample included Asia Cell for 2012–2023, as use models for measuring intellectual capital Public (2000) and developed in models MVAIC, and this includes six for capital, "where intellectual capital efficiency’s (ICE) connection to human capital (HC), HCE human capital efficiency, SCE structural capital efficiency, RCE relational capital efficiency, HC is employees’ salaries and wages, and RC is marketing, selling, and advertising expenses." To measure the sustainable performance as a dependent variable and to test the hypotheses, a statistical program (SPSS) was used. The results of our research show the impact of intellectual capital in various types or forms on the company’s performance and sustainability.